On certain polynomial systems involving Stirling numbers of second kind. (March 2022) - Castro-Jiménez, F.J.; Cobo Pablos, H.
Abstract: We solve a special type of linear systems with coefficients in multivariate polynomial rings. These systems arise in the computation of b-functions with respect to weights of certain hypergeometric ideals in the Weyl algebra.